Upaya Meningkatkan Disiplin Tenaga Pendidik Melalui Penerapan Metode Penugasan - tohir, mohd (Komunitas Manajemen Kompetitif, 2017)
Abstract: Teacher discipline is a requirement in implementing the learning plan in school. Teachers become the spearhead of service required to be an example and role model for learners. Examples and examples of this teacher can be seen from the discipline of teachers in implementing the work plan of teaching and learning in schools. Through classroom action research using assignment method by applying 3 cycles and data analyzed descriptively it can be proven that the assignment method for the teacher in the form of assignment of the implementation of the lesson plan by giving the award proves the gradual improvement of teacher work discipline in school. Keywords: Discipline of educator, method of assignment